2022
DOI: 10.3389/fpubh.2021.829367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brisk Walking on Health-Related Physical Fitness Balance and Life Satisfaction Among the Elderly: A Systematic Review

Abstract: BackgroundAlthough the elderly frequently engages in brisk walking as a form of exercise, little has been reported in the literature about the effect of brisk walking on health-related physical fitness, balance, and overall life satisfaction.ObjectivesThe purpose of this systematic review is to determine the effect of brisk walking on the elderly's health-related physical fitness, balance, and life satisfaction.DesignWe conducted a comprehensive search from the PubMed, Web of Science, Scopus, and SPORTDiscus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Higher prevalence of functional limitations could be associated with the absence of physical activities in the older people, and this study showed that about three quarters of them lacking physical activities in daily life. Previous studies have proven that physical activities could improve cardiorespiratory fitness, muscular strength, body composition, balance, flexibility, and muscular endurance in the older people (31). Hence in the future, more access to physical exercise should be provided to the older people to strengthen their functional health.…”
Section: Discussionmentioning
confidence: 99%
“…Higher prevalence of functional limitations could be associated with the absence of physical activities in the older people, and this study showed that about three quarters of them lacking physical activities in daily life. Previous studies have proven that physical activities could improve cardiorespiratory fitness, muscular strength, body composition, balance, flexibility, and muscular endurance in the older people (31). Hence in the future, more access to physical exercise should be provided to the older people to strengthen their functional health.…”
Section: Discussionmentioning
confidence: 99%
“…Walking as a way of improving the health of seniors has been studied already for a long time. The beneficial effect of walking on various body systems has been demonstrated in many studies over the years [25,[46][47][48][49]. Many of the literary resources therefore agree that aerobic exercise in various forms, including walking, positively affects the lung function in seniors [37,40,50].…”
Section: Discussionmentioning
confidence: 99%
“…Adults are recommended to walk 10,000 steps per day to maintain good health [ 8 ]. Further, the World Health Organization recommends 150–300 minutes of moderate to high intensity or at least 75–150 minutes of vigorous-intensity physical exercise per week [ 9 ]; however, determining the optimal frequency, intensity, time, and type (known as ‘FITT’) one should perform a particular exercise can be difficult [ 10 ]. For healthy adults aged 41–85 years, a step frequency of 100–130 steps/min and 2000–9000 steps per day has been found to produce an optimal exercise level of 3–6 MET [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paced walking (or brisk walking) represents walking at a brisk pace, usually 120 steps/min or greater, and is recognised as a suitable form of cardio workout [ 15 ]. A previous systematic review has demonstrated that a brisk-walking intervention can improve cardiorespiratory fitness, muscular strength, and body composition in older adults [ 10 ]. On the other hand, music-synchronised walking (or beat-synchronised walking) refers to walking at varied cadences in time with musical beats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation